Secret Seven Mystery Of Theatre Ghost - Pamela Butchart, Enid Blyton & Tony Ross
A second, action-packed Secret Seven adventure by prize-winning author Pamela Butchart, brilliantly illustrated by Tony Ross. The Secret Seven are excited to be chosen as extras in a local play, but during the opening performances things go seriously wrong. Could someone be trying to sabotage? The cast and crew are adamant that a theatre ghost must be causing the mysterious accidents, but the Seven aren't convinced. It's up to the gang and their spaniel Scamper to find out who is really behind the mischief - and why! Set in the same world and time as the original stories by Enid Blyton, both Mystery of the Skull and this fantastic new book satisfyingly extend the series for fans old and new. Both stories are brought to life by Tony Ross's brilliant illustrations throughout. Join the Secret Seven for more mystery, excitement, friendship and FUN than ever before! Read all 15 stories in the original Secret Seven series ...Also look out for Secret Seven Brain Games - a fun and tricky puzzle book! *Enid Blyton , The Secret Seven and Enid Blyton's signature are registered trade marks of Hodder & Stoughton Limited. No trade mark or copyrighted material may be reproduced without the express written permission of the trade mark and copyright owner.